Shaggy aorta: ideal substrate for disaster. Updated review - Velarde-Acosta, Kevin (2024)
Shaggy aorta (SA) is characterized by a critical and extensive atheromatous disease of the thoracic and abdominal aorta. This degenerative and dangerous pathology is the result of the confluence of multiple modifiable and non-modifiable risk factors. The clinical importance of this pathology relies on the various syndromes that can develop from its etiopathogenesis, which generates great morbidity and mortality in the affected patients. In this document, we present an updated and detailed review of this entity, developing aspects of its pathophysiology, diagnosis, including the importance of multimodal imaging, and its therapeutic approach. Finally, we present the clinical settings of patients with SA in different aortic scenarios (aortic dissection, ulcerated plaques, and thrombosed aneurysms) that denote the nature of this disease and its high mortality.